Juridical Review of Power of Attorney For Implementing Liability Rights (Skmht) as a Media For Binding Guarantee in the Credit Take Over Process in Banking Companies - Sastradinata, Dhevi Nayasari; Maulidah, Tuhfatul; Romadhoni, Suci (Universitas Islam Lamongan, 2021)
ABSTRACT with the aim of producing library materials and an overview of the validity period of the SKMHT and the Legal Consequences of the issuance of the Power of Attorney to impose Mortgage Rights (SKMHT) in the Take Over process. By using the type of normative legal research and sociological or empirical legal research.